2021
DOI: 10.5334/joc.183
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Individual Differences in Recognizing Idiomatic Expressions in Context

Abstract: Written language comprehension requires readers to integrate incoming information with stored mental knowledge to construct meaning. Literally plausible idiomatic expressions can activate both figurative and literal interpretations, which convey different meanings. Previous research has shown that contexts biasing the figurative or literal interpretation of an idiom can facilitate its processing. Moreover, there is evidence that processing of idiomatic expressions is subject to individual differences in lingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Language and linguistic challenges, such as idiomatic expressions or cultural references, could pose difficulties for the AI models in accurately comprehending and responding to the questions, whereas the residents' human intuition and linguistic skills give them an advantage. 14 We found the explanation of the AI in supporting the answers was accurate in less than 50% of the cases. The AI models may have inherent limitations in understanding the specific nuances, details, or contextual elements of the topics being evaluated.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Language and linguistic challenges, such as idiomatic expressions or cultural references, could pose difficulties for the AI models in accurately comprehending and responding to the questions, whereas the residents' human intuition and linguistic skills give them an advantage. 14 We found the explanation of the AI in supporting the answers was accurate in less than 50% of the cases. The AI models may have inherent limitations in understanding the specific nuances, details, or contextual elements of the topics being evaluated.…”
Section: Discussionmentioning
confidence: 74%
“…Language and linguistic challenges, such as idiomatic expressions or cultural references, could pose difficulties for the AI models in accurately comprehending and responding to the questions, whereas the residents' human intuition and linguistic skills give them an advantage. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Discussions of processing speed in linguistic research are found primarily in studies of aging and language, given that a slowing in processing speed is a well-established component of cognitive aging (Eckert, 2010;Rogalski et al, 2011;Salthouse, 1996;Soble et al, 2016). However, processing speed correlates with picture naming, auditory lexical decision, and idiom processing in young adults as well (Hintz et al, 2020;Tilmatine et al, 2021). It has been proposed to index the ease/speed with which incoming input can be integrated into unfolding representations (Huettig & Janse, 2016).…”
Section: Processing Speedmentioning
confidence: 99%